The Dynamic Scleral Extracellular Matrix Alterations in Chronic Ocular Hypertension Model of Rats - Qiu, Chen; Yao, Jing; Zhang, Xi; Zhang, Rong; Sun, Xinghuai; Qian, Shaohong (Frontiers in Physiology, 2020)
Intraocular pressure (IOP) generates stress and strains in the laminar cribrosa and sclera, which may affect the development and progression of glaucoma. Scleral stiffness and material components have changed under the elevated IOP. However, the detailed components’ changes of the hypertensive sclera are not well understood. In this study, we aimed to investigate the changes of the main components in scleral extracellular matrix (ECM) and matrix metalloproteinase 2 (MMP2), and their relationship with time under chronic elevated IOP in Sprague-Dawley rats. Ocular hypertension model was established in the right eyes by anterior chamber injection with 0.3% carbomer solution. The left eye was used as contralateral control. Immunofluorescent imaging of tissue frozen sections, western blot analysis and qPCR were performed to detect the expressions of type Ⅰ collagen (COL1), elastin, and MMP2 in sclera. The ocular hypertension model was successfully established. As compared to the left eyes, the immunofluorescence imaging, western blot analysis and qPCR showed that COL1, elastin and MMP2 were significantly increased in the right eyes at 1 week (all P < 0.05). At 2 weeks, COL1 in the right eyes tended to be lower than that in the left eyes, while elastin and MMP2 was still higher (all P < 0.05) in the right eyes. When IOP was elevated for 4 weeks, both COL1 and MMP2 were lower than that in the left eyes (all P < 0.05), while elastin between the two eyes was similar (P > 0.05). Under this 4-week hypertensive state, COL1 and elastin were initially elevated at 1 week, and then obviously reduced from 2 weeks to 4 weeks. Consistently, MMP2 was gradually increased with the peak at 2 weeks, and then decreased at 4 weeks. In conclusion, the chronic elevated IOP induced dynamic scleral ECM alterations in rats in a pressure- and time-dependent way. MMP2 may play an important role in the balance between ECM synthesis and degradation and could potentially be a novel target for glaucoma intervention.